2020
DOI: 10.3390/ijerph17082961
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Disease, the Built Environment, and Unequal Health Risks in the 500 Largest U.S. Cities

Abstract: Health is increasingly subject to the complex interplay between the built environment, population composition, and the structured inequity in access to health-related resources across communities. The primary objective of this paper was to examine cardiometabolic disease (diabetes, cardiovascular diseases, stroke) markers and their prevalence across relatively small geographic units in the 500 largest cities in the United States. Using data from the American Community Survey and the 500 Cities Project, the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…One study found a significantly lower prevalence of asthma, arthritis, diabetes, hypertension, and obesity in affluent counties compared with the least affluent ones (7). Another study showed that people with less than a high school education had nearly twice the odds of having diabetes compared with those with a college degree (8). Across large US cities, rates of stroke and hypertension are concentrated in census tracts with a high proportion of Black residents, old homes with low market value, and people receiving government assistance (9).…”
Section: Introductionmentioning
confidence: 99%
“…One study found a significantly lower prevalence of asthma, arthritis, diabetes, hypertension, and obesity in affluent counties compared with the least affluent ones (7). Another study showed that people with less than a high school education had nearly twice the odds of having diabetes compared with those with a college degree (8). Across large US cities, rates of stroke and hypertension are concentrated in census tracts with a high proportion of Black residents, old homes with low market value, and people receiving government assistance (9).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the principal factors that impact health is an important theme in obesity research [1][2][3]. Multiple health behaviors and environmental conditions contribute to the obesity crisis [4].…”
Section: Introductionmentioning
confidence: 99%
“…A critical barrier in obesity prevention and treatment is determining which individual, social, and environmental factors shape our health [ 1 , 2 , 3 ]. A person’s behavior and the multiple environments they navigate cause obesity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%